REINSURANCE IN MEXICO, MORAL HAZARD AND ASIMETRIC INFORMATION - Cassab, Eduardo (2005)
This paper attempts to investigate Moral Hazard and Asymmetric Information between Insurance and Reinsurance Companies in the Mexican Insurance Industry. Empirical results revealed by the analysis of information asymmetries that occur in the Mexican Insurance Market, describe how these information asymmetries can lead to adverse selection problems.